Mitigating the Risk of Ship Accidents with an Integrated Approach to Maritime Safety Management - Latt, Nyein Zin (Maritime Park: Journal of Maritime Technology and Society, 2024)
This research explores an integrated approach in maritime safety management to reduce the risk of ship accidents. With the increasing volume of maritime traffic and the complexity of shipping operations, ship safety has become a critical aspect that must be considered. This study identifies and analyzes various safety technologies and strategies that have been implemented in the maritime industry, such as Automatic Identification Systems (AIS), Vessel Traffic Management (VTS), Weather Early Warning Systems, and crew training and certification programs. Data collected through literature reviews and case studies show that the application of this advanced technology significantly improves shipping safety and reduces accident incidents.